2019
DOI: 10.1016/j.neuron.2018.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Engagement of Pulvino-cortical Feedforward and Feedback Pathways in Cognitive Computations

Abstract: Computational modeling of brain mechanisms of cognition has largely focused on the cortex, but recent experiments have shown that higher-order nuclei of the thalamus participate in major cognitive functions and are implicated in psychiatric disorders.Here, we show that a pulvino-cortical circuit model, composed of the pulvinar and two cortical areas, captures several physiological and behavioral observations related to the macaque pulvinar. Effective connections between the two cortical areas are gated by the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(113 citation statements)
references
References 100 publications
4
102
0
Order By: Relevance
“…If the real part of the eigenvalues is negative, the deterministic equations have damped oscillations; the corresponding stochastic Wilson-Cowan network operates then in the Transient synchrony regime (also know as the quasi-cycle regime) where oscillations, albeit irregular ones, are sustained by noise. This regime is very popular and has already been suggested to underlie frequency-specific, hierarchical corticocortical 51,52 and thalamocortical 53 interactions, although with a reduced level of complexity. The analytical treatment in the present study might very well serve as a starting point to understand these large-scale interactions at a more fundamental level.…”
Section: Resultsmentioning
confidence: 99%
“…If the real part of the eigenvalues is negative, the deterministic equations have damped oscillations; the corresponding stochastic Wilson-Cowan network operates then in the Transient synchrony regime (also know as the quasi-cycle regime) where oscillations, albeit irregular ones, are sustained by noise. This regime is very popular and has already been suggested to underlie frequency-specific, hierarchical corticocortical 51,52 and thalamocortical 53 interactions, although with a reduced level of complexity. The analytical treatment in the present study might very well serve as a starting point to understand these large-scale interactions at a more fundamental level.…”
Section: Resultsmentioning
confidence: 99%
“…The pulvinar is part of the "thalamic matrix" and projects diffusely to the cortex, playing a significant role in cognition and attentive stimulus processing (87). Recent studies have confirmed that the pulvinar can facilitate attention-related communication across widespread neuronal networks including higher-order sensory cortices (88) and, as mentioned before, it has a clear role in photophobia. In the future, neuroimaging studies focused on these nuclei will help clear the role of thalamic dysfunction in visual snow.…”
Section: Toward a Model For Visual Snowmentioning
confidence: 86%
“…Recent studies provided theoretical, connectional, functional, and modeling evidence to support the notion of a “cognitive thalamus,” thereby indicating the critical role exerted by the region in control of cognition. The “cognitive thalamus” hypothesis postulates that the region is a key modulating hub for corticocortical interactions . According to the hypothesis, high‐order thalamic nuclei (ie, associative and posterior nuclei) exhibit critical functional and structural connections with the DMN, thereby affecting network activity and, ultimately, cognition.…”
Section: Thalamocortical Dysrhythmia As the Driver Of Dmn Decouplingmentioning
confidence: 99%